1994
DOI: 10.1128/mcb.14.12.8028
|View full text |Cite
|
Sign up to set email alerts
|

A family of complex tandem DNA repeats in the telomeres of Chironomus pallidivittatus.

Abstract: A family of 340-bp tandem telomere-associated DNA repeats is present in 50-to 200-kb (18,30,48). Thus, there is no absolute topological distinction between the two types of DNA. One telomeric function, for which telomerase is responsible, is to restore DNA that is lost after replications (22,23). Another is the maintenance of chromosomal integrity (see reference 2 and references therein) believed to be related to the propensity of telomeric DNA to form secondary structures (see reference 6 and references th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 58 publications
1
43
0
Order By: Relevance
“…Species that had no cross-hybridization included the five Diptera and three of the eight Coleoptera studied. Lack of cross-hybridization does not prove that a species lacks telomerase; however, at least two Diptera, D. melanogaster and Chironomous pallidivittatus, are known to have chromosome end sequences that differ significantly from the simple repeats generated by telomerase (2,23,24). Thus these species have either lost telomerase or, as we have argued (3,25), their telomerase has undergone significant evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species that had no cross-hybridization included the five Diptera and three of the eight Coleoptera studied. Lack of cross-hybridization does not prove that a species lacks telomerase; however, at least two Diptera, D. melanogaster and Chironomous pallidivittatus, are known to have chromosome end sequences that differ significantly from the simple repeats generated by telomerase (2,23,24). Thus these species have either lost telomerase or, as we have argued (3,25), their telomerase has undergone significant evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Telomeres in D. melanogaster are composed of the retrotranposons, HeT-A and TART, whereas telomeres in C. pallidivittatus and Chironomous thummi are composed of large complex repeats (23,24). The mechanism by which the Chironomous repeats are generated is not known.…”
Section: Discussionmentioning
confidence: 99%
“…D. melanogaster actually lacks telomeric repeats, as shown by the failure to cross-hybridize with various oligonucleotides whose design is based on several telomeric sequences [28±30]. In addition, two other Diptera, Chironomus [31,32] and Anopheles [7], also seem to have no (TTAGG) n repeats. That we could not detect telomerase activity in two Drosophila and one Sarcofaga cell lines in this study, is consistent with the observed telomeric repeat missing in Diptera.…”
Section: Discussionmentioning
confidence: 99%
“…We first converted the blocks of repeats in the extracted DNA to monomers with HaeIII, which restricts the majority of repeats in all subfamilies (7,27). The initial part of L4, containing subfamily-specific restriction sites (7,34), lies in the middle of the released monomers. We used primers on both sides of this region for amplification.…”
Section: Figmentioning
confidence: 99%
“…In the case of D3 there is a second difference, i.e., one large region has become substituted for another one. Telomeres differ in subfamily composition (8,34). When D3 is present together with other kinds of repeats, it is always the most peripheral unit (34).…”
mentioning
confidence: 99%